Reduction of Cd accumulation in pak choi (Brassica chinensis L.) in consecutive growing seasons using mercapto-grafted palygorskite. Issue 56 (17th September 2018) - He, Lizhi; Li, Na; Liang, Xuefeng; Yin, Xiuling; Huang, Qingqing; Wang, Lin; Sun, Yuebing; Xu, Yingming
Abstract : MP significantly reduced Cd accumulation in the shoots of pak choi in comparison to the control, in consecutive growing seasons, and the minimum Cd contents were less than the maximum permitted level proposed by the Codex Alimentarius Commission. Abstract : Cd contamination in agricultural fields poses a potential human health risk via food chain exposure. Proper remediation methods are critical to ensure the adequate safety of agricultural food products. In the current study, mercapto-grafted palygorskite (MP), a novel immobilization agent, was selected for the remediation of Cd-contaminated acid soils in pot experiments. Pak choi was used as the model plant. MP significantly reduced Cd accumulation in the shoots and roots of pak choi grown in Xiangtan and Guiyang soils in comparison to the control, in consecutive growing seasons, and the minimum Cd contents in shoots were less than the maximum permitted level proposed by the Codex Alimentarius Commission of FAO and WHO. Further, MP decreased the phytoavailable Cd content in soils determined using the diffusive gradient technique in thin-films in consecutive growing seasons with the maximum reductions of 86.26% and 89.51% respectively. These findings indicated that MP had a remarkable Cd immobilization efficiency in soils. MP had no obvious promotion impact on the pH value of either soil sample, but decreased the zeta potentials of both soil samples significantly, and then resulted in increases of the maximum sorption amounts of Cd of both soil samples. The results indicated MP could achieve remediation of Cd-contaminated soil by enhancing the sorption of Cd contaminants and the chemical sorption of Cd 2+ . The available sulfur content in both soils increased and soil enzyme activities, such as that of urease, were enhanced, thereby alleviating Cd-induced oxidation. These improvements of the index of soil environmental and biological qualities indicated that MP was environmentally friendly and compatible. The high performance of MP even at a small dosage suggested that when scaled up to agricultural operations over a large-area, MP had great potential to reduce Cd accumulation in vegetables, thereby ensuring the food safety of vegetables.